Characterization of non-contact measurements of electrolyte concentrations using a printed mutual-capacitive sensor film. (1st March 2019) - Iwata, Shiro; Imawaka, Naoto; Yoshino, Katsumi; Nomura, Ken-ichi; Horii, Yoshinori; Kaji, Ryosaku; Ushijima, Hirobumi
Abstract: We have characterized a non-contact measurement system to concentrations of electrolytic solutions using a sensor film that is pasted on the outer surface of the solution vessel. This sensor film has asymmetrically sized circular electrodes printed facing each other on the both faces of substrate, and operates as a mutual-capacitive sensor. This measurement system shows the response depend on the strength of the electrolyte dissociation. In addition, it is found that the resolution and the sensing range could be controlled by adjusting the frequency of the applied voltage in the range from 10 kHz to 1 MHz.